Shift in Immune Parameters After Repeated Exposure to Nanoplastics in the Marine Bivalve Mytilus - Auguste, Manon (Front Immunol, 2020)
Bivalves are widespread in coastal environments subjected to a wide range of environmental fluctuations: however, the rapidly occurring changes due to several anthropogenic factors can represent a significant threat to bivalve immunity. The mussel Mytilus spp. has extremely powerful immune defenses toward different potential pathogens and contaminant stressors. In particular, the mussel immune system represents a significant target for different types of nanoparticles (NPs), including amino-modified nanopolystyrene (PS-NH(2)) as a model of nanoplastics. In this work, the effects of repeated exposure to PS-NH(2) on immune responses of Mytilus galloprovincialis were investigated after a first exposure (10 μg/L; 24 h), followed by a resting period (72-h depuration) and a second exposure (10 μg/L; 24 h). Functional parameters were measured in hemocytes, serum, and whole hemolymph samples. In hemocytes, transcription of selected genes involved in proliferation/apoptosis and immune response was evaluated by qPCR. First exposure to PS-NH(2) significantly affected hemocyte mitochondrial and lysosomal parameters, serum lysozyme activity, and transcription of proliferation/apoptosis markers; significant upregulation of extrapallial protein precursor (EPp) and downregulation of lysozyme and mytilin B were observed. The results of functional hemocyte parameters indicate the occurrence of stress conditions that did not however result in changes in the overall bactericidal activity. After the second exposure, a shift in hemocyte subpopulations, together with reestablishment of basal functional parameters and of proliferation/apoptotic markers, was observed. Moreover, hemolymph bactericidal activity, as well as transcription of five out of six immune-related genes, all codifying for secreted proteins, was significantly increased. The results indicate an overall shift in immune parameters that may act as compensatory mechanisms to maintain immune homeostasis after a second encounter with PS-NH(2).